1978
DOI: 10.1152/ajpheart.1978.234.3.h244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitroglycerin on cardiac function and regional blood flow distribution in conscious dogs

Abstract: The effects of intravenous infusion of nitroglycerin (NTG), 8 and 32 microgram/kg.min for 7 min, and of sublingual NTG, 1.2 mg, were examined on direct and continuous measurements of systemic, coronary, and regional hemodynamics, left ventricular (LV) dimensions, pressures, and myocardial contractility in conscious dogs. NTG induced sustained reductions in LV dimensions and transient increases in heart rate and dP/dt, and decreases in mean arterial pressure. Initially NTG increased cardiac output and flows to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 0 publications
6
21
1
Order By: Relevance
“…Nitroglycerin is a vasodilator agent that is widely used in the treatment of anginal disease whereas nitroprusside is used in the management of hypertensive emergencies and for afterload reduction in patients with left heart failure and myocardial infarction (1)(2)(3)(4). Although the systemic vascular responses to nitroprusside and nitroglycerin have been intensively investigated (5)(6)(7)(8), the actions of these substances on the pulmonary circulation have received less attention and little, if anything, is known about the effects of these agents on the pulmonary veins (9)(10)(11)(12)(13). Nitroprusside and nitroglycerin have been reported to decrease pulmonary arterial pressure in patients with congestive heart failure (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Nitroglycerin is a vasodilator agent that is widely used in the treatment of anginal disease whereas nitroprusside is used in the management of hypertensive emergencies and for afterload reduction in patients with left heart failure and myocardial infarction (1)(2)(3)(4). Although the systemic vascular responses to nitroprusside and nitroglycerin have been intensively investigated (5)(6)(7)(8), the actions of these substances on the pulmonary circulation have received less attention and little, if anything, is known about the effects of these agents on the pulmonary veins (9)(10)(11)(12)(13). Nitroprusside and nitroglycerin have been reported to decrease pulmonary arterial pressure in patients with congestive heart failure (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Nitroprusside, used in this study, reduces directly venous tone (23), therefore causing hypotension by reducing cardiac preload (24) and filling. Previous studies in sheep (2-4) have shown that fetal hemorrhage is associated first with an increase then with a rapid decrease in fetal HR as arterial blood pressure decreases further.…”
Section: Discussionmentioning
confidence: 99%
“…Since continuous dosing of nitrates facilitates the maintenance of a constant high blood concentration, this procedure is routinely used to treat unstable angina or heart failure; however, it is known that nitrate tolerance appears within 24 h with respect to improvement in pulmonary wedge pressure or exercise tolerance (3,5). As a strategy to overcome such tolerance, eccentric dosing has been recommended (9,14).…”
Section: Tolerance To Nitratesmentioning
confidence: 99%
“…With respect to systemic circulation and pulmonary circulation, it has been reported that 24-h administration of nitrates induces nitrate tolerance (3). With respect to their direct actions on coronary circulation, nitrates dilate the coronary arteries (4), increasing coronary blood flow (CBF) (5). In many studies examining nitrate tolerance in patients with ischemic heart disease, improvement in exercise tolerance was used as an index (6), and thus the actions of nitrates on the coronary circulation and the appearance of nitrate tolerance remain unclear in many respects.…”
Section: Introductionmentioning
confidence: 99%